"Providence, RI, May 1924" - Rorke Family (1924)
Hilda (Forward) Pike with sister Ernestine (Forward) Pike and Ernestine's sons Arthur Jr., baby Ralph and Ernest, in a street in Providence, Rhode Island. Cataloguer's title. Ernestine (Forward) Pike (1887-1950), daughter of Ernest Edward Forward and Tryphena (Butt) Forward, was born at Carbonear on 24 April 1887. She married Arthur S. Pike at Carbonear on 25 September 1913 and had 3 sons: Ernest Fletcher Pike, Arthur Pike Jr. and Ralph Forward Pike. She died at Providence, Rhode Island on 22 March 1950. Ernestine's sister Hilda Samways (Forward) Pike (1889-1982) was born on 5 June 1889. She married her sister Ernestine's former husband, Arthur S. Pike, on 5 June 1951, over a year after her sister died. Hilda died in 1982. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.